Optimizations of r GO supported CdS photo-electrocatalyst for dissociation of water - Ranjan R.; Sinha A.S.K. (My University, 2025)
The paper reports fabrication of electrode containing rGO supported CdS catalyst for photoelectrochemical reduction of water to hydrogen. The reduction of GO to r GO was carried out electrochemically in situ. The catalyst which contained 10 wt % GO with CdS showed the best activity. Catalysts were characterized by XRD, FTIR, DRS, SEM, TEM, SED, XPS, PL, EIS and Mott-Schottky analysis. It is reported that incorporation of r GO to CdS resulted into formation of heterojunction at the interface of CdS and rGO by a chemical interaction between the two. Consequently, a greater band bending, a higher charge carrier density, a low resistance for electronic mobility and low recombination rate result in. The high activity of the catalyst is due to the above mention attributes. These effects become prominent with the increase in the loading of GO, however, any loading in excess of 10 wt % resulted into its shielding of CdS which adversely affected the activity. © 2019 Hydrogen Energy Publications LLC